PROSPECTS OF USING MODERN PEDAGOGICAL TECHNOLOGIES IN TEACHING PHYSICS AND ASTRONOMY - PISA INTERNATIONAL ASSESSMENT PROGRAM - Mirzayeva Umidaxon Murodjon qizi (Western European Studies, 2024)
This article provides statistical information about the international assessment program, modern educational programs, creative thinking, and the promotion of scientific literacy.
Keywords: international standards; statistics; PISA; TIMSS